The school director's innovativeness, political skills and integrity towards policy framework for agenda setting - Bonotan, Amelia M.; Lapiz, Gary B. (2015)
This descriptive-correlational research study seeks to determine the relationship between technical/vocational school directors' political skills and integrity and their innovativeness. Amidst the competitiveness of the global market, school leaders are challenegd to be up to date with the trends and innovations to enhance students' job readiness and employability. Two parallel Likert-type questionnaires developed by the researchers, which wew subjected to content validation by education experts and to reliability tests (Cronbach a=0.95) were administered to 159 school directors, faculty members, administrative officers and finance officers of 40 technical schools in the National Capital Region. Results revealed that the innovativeness of directors positively related to their integrity and political skills. Based on the results and in line with the thrust of the Philippine Development Plan 2011-2016, the researchers proposed a policy paradigm for agenda setting to aid in the formulation and implementation of policies in the supervision and administration of technical vocational institutions.
Keywords: Educational leadership -- Evaluation; School administration; Public administration; Educational innovations